Transforming Brazil - Ioris, Rafael Rossotto., author.
1 online resource (x, 266 pages)
Keywords: "In this book, Rafael R. Ioris critically revisits the postwar context in Brazil to reexamine traditional questions and notions pertaining to the nature of Latin America's political culture and institutions. It was in this period that the region lived some of its most intense and successful experiences of fast economic growth, which was paradoxically marred by heightened ideological divisions, political disruptions, and the emergence of widespread authoritarian rule. Combining original sources of political, diplomatic, intellectual, cultural, and labor histories, Ioris provides a comprehensive history of the fruitful debates concerning national development in postwar Brazil, a time when the so-called country of the future faced one of its best moments for consolidating political democracy and economic prosperity. He argues that traditional views on political instability have been excessively grounded on an institutional focus, which should be replaced by in-depth analysis of events on the ground. In so doing, he reveals that as national development meant very different things to multiple different social segments of the Brazilian society, no unified support could have been provided to the democratically elected political regime when things rapidly became socially and politically divisive early in the 1960s"--